Գիտելիքի զարգացման մեխանիզմների բացահայտման էվոլյուցիոնիստական հայեցակարգը - Հակոբյան, Ա.
В статье рассматривается проблема движущих факторов и механизмов развития науки. Обосновывается, что под воздействием идей универсального эволюционизма, основная тенденция методологических концепций современного научного познания переходит от исследования завершенного знания к исследованию закономерностей возникновения нового знания. The issue of the mechanisms and driving factors of the development of science is analyzed in the article and it is substantiated that under the influence of universal evolutionism, the basic trend of methodological concept of nowadays scientific perception is the transition from the study of perfect knowledge towards the exploration of the regularities of the emergence of new science.
Keywords: Գիտության փիլիսոփայություն